Harry Clark, IPCC WGIII release event, Washington DC - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Priorities for best practices and capacity building -- Harry Clark, New Zealand Agricultural Greenhouse Gas Research Centre, GRA Livestock Research Group, IPCC author Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC